Workforce development for U.S. hydropower: key trends and findings - Keyser, David, author; Tegen, Suzanne, author; National Renewable Energy Laboratory, publisher (Colorado State University. Libraries, 2019)
The purpose of this report is to provide a brief assessment of the current U.S. hydropower industry workforce and educational programs, as well as potential future hydropower workforce needs. This report is based on data collected in 2016 for the U.S. Department of Energy (DOE) by Navigant Consulting and the National Renewable Energy Laboratory (NREL), which included a 2014 survey of hydropower employers to assess future workforce needs for potential growth scenarios.
Report in collaboration with the National Renewable Energy Laboratory (nrel.gov/publications).
Keywords: Water-power; Employment; Labor supply; Renewable energy sources -- Law and legislation -- United States